Performance Analysis of Interference Limited Hybrid RF/FSO Satellite-Terrestrial Networks - Upadhya, Abhijeet; Goel, Anu (International Conference on Signal Processing and Communication (Online), 2025)
The letter investigates the performance of Satellite-terrestrial hybrid radio frequency (RF)/ free space optics (FSO) communication system. In this work, two links are considered to connect the terrestrial node with a Satellite in space. One link follows the RF spectrum which is used as an standby arrangement. The main link is the one where optical link is established through the wireless medium between the ground device and the Satellite. The proposed model also includes the effect of multiple RF interferers operating in the vicinity of the terrestrial node. The RF link has been modeled with the aid of Rician shadowing statistical model whereas the FSO link under-goes atmospheric turbulence with misalignment errors, modeled as Gamma-Gamma distribution. Closed-form expression for the outage probability has been derived in the work considering the impact of interference.